Identifikasi Staphylococcus sciuri dan S. hominis pada Ikan Kerapu di Pasar Ikan Kedonganan dengan Analisis Sekuen 16S rRNA - Besung, I Nengah Kerta; Agustiani, Ni Komang Eka; Mahardika, I Gusti Ngurah Kade (Jurnal Veteriner, 2019)
Grouper are reef fish which can be cultivated because highly commercial value. There are many different types of bacteria in the digestive tract of grouper, one of them is Staphylococcus. Staphylococcus sp. is a Gram positive, non spora, non motile, and facultative anaerobic. Most of Staphylococcus sp. are pathogenic in human and animals. The purpose of this study was to identify the species Staphylococcus sp. on grouper sold at the Kedonganan fish market, Kuta District, Badung Regency, Bali Province based on 16S rRNA sequence analysis. This study used grouper feces as a samples from 20 fishes. Staphylococcus sp. from feces were cultured in media Blood Agar. Sequence analysis 16S rRNA Staphylococcus sp. was conducted with PCR and sequencing method. This study can identify the bacteria Staphylococcus sciuri and Staphylococcus hominis.